A Perspective on the Use of Hydroxyapatites to Improve the Dissolution Behavior of Poorly Water-Soluble Piretanide - Valeria Friuli; Claudia Loi; Giovanna Bruni; Lauretta Maggi; Marcella Bini (MDPI AG, 2024)
Background/Objectives: Interest in drug delivery systems (DDS) based on inorganic substrates has increased in parallel with the increase in the number of poorly water-soluble drugs. Hydroxyapatite is one of the ideal matrices for DDS due to its biocompatibility, low cost, and ease of preparation. Methods: We propose two doped hydroxyapatites, one with Ba on Ca sites another with Si on P sites, with the aim of improving the dissolution rate of piretanide, a diuretic, poorly water-soluble drug. The hybrids were characterized by different physical-chemical techniques, and their formation was demonstrated by infrared spectroscopy, thermal analysis, and electron microanalysis, as well as by comparing the results with those obtained on physical mixtures of HAPs and properly prepared piretanide. Results: Both the hybrids improved the piretanide dissolution rate compared with the physical mixtures and the drug alone. The dose was completely solubilized from the Si-doped hybrid in about 5 min in the three fluids considered. This remarkable improvement can be explained by an increase in the wettability and solubility of the drug loaded in the drug-carrier systems. Conclusions: Different experimental techniques, in particular spectroscopy and electronic microanalysis, proved the successful loading of piretanide onto doped HAP. Pharmaceutical measurements demonstrated rapid drug release in different fluids simulating gastrointestinal conditions after oral administration. These hybrid systems could be a very promising platform for drug delivery.